The effect of social media campaign on parental knowledge, attitudes and practices regarding the use of children car seats in the Gulf region - Eman A. Bakhurji; Albandari M. Alqahtani; Ezdehar M. Alwashmi; Manayer S. Husain; Balgis O. Gaffar (BMC, 2023)
Abstract Background Motor vehicle crashes (MVCs) are the leading cause of child deaths in the Gulf Cooperation Council. This study aimed to investigate the effect of a social media educational campaign on parents' knowledge of child safety seats. Methods We conducted a pre-post interventional study as an online educational module in Arabic and English. The module link was shared on social media and was accompanied by a pre-post survey that included questions about demographics, knowledge, and practices of car seat use. Results A total of 303 participants completed the campaign, with 23.8% fathers and 76.2% mothers answered the survey. The majority of participants were from Saudi Arabia (95.7%), while 4.3% were from other Gulf Cooperation Council (GCC) countries. Most parents agreed on the importance of organizing awareness campaigns and having a law to enforce the use of car seats. The pre-survey mean knowledge score was 11.64, which significantly increased to 13.1 in the post-survey (p < 0.001). Conclusions The intervention of the educational campaign through social media resulted in a significant increase in parents' knowledge and awareness of the importance of using car seats correctly. This study highlights the potential effectiveness of social media campaigns in improving parents' knowledge and awareness of child safety seats.